Prompting the Benefit of the Doubt: The Joint Effect of Auditor‐Client Social Bonds and Measurement Uncertainty on Audit Adjustments - KACHELMEIER, STEVEN J.; VAN LANDUYT, BEN W. (Journal of Accounting Research, 2017)
ABSTRACT We design an incentivized experiment to test whether measurement uncertainty elevates the risk that social bonds between auditors and reporters compromise audit adjustments. Results indicate that, when audit evidence is characterized by some residual uncertainty, the adjustments our auditor‐participants require are sensitive to whether auditors have an opportunity to form a modest but friendly social bond with reporters. In contrast, although auditors do not adjust fully even when misstatements are known with certainty, social bonding has no effect in this scenario. Accordingly, our experiment contributes beyond the main effects of social bonding and measurement uncertainty demonstrated in prior research by showing that these forces interact. A practical implication is that regulators and practitioners should consider both the technical and the social challenges facing audits of complex estimates.